A scoping review on the influencing factors and development process of professional identity among nursing students and nurses - Mao, Aimei; Lu, Su-e; Lin, Yan; He, Miao (Journal of professional nursing, 2021)
Professional identity (PI) is culturally shaped. It is associated with a sufficient and stable workforce of professionals. China has a relatively low ratio of nursing professionals to its population. This scoping review aims to obtain comprehensive knowledge of the influencing factors and PI development process among nursing students and nurses in China. A scoping review was conducted. The most common Chinese databases, China National Knowledge Infrastructure and Wanfang Data were searched for publications in Chinese. The databases of EBSCOhost and ProQuest Dissertation & Thesis Global (Full Text) were searched for publications in English. After screening the title and abstract of the articles and further assessing the full text of the articles identified after the initial screening, 53 articles were included for analysis. The influencing factors to PI development in nursing were grouped into four dimensions: personal, family, institutional, and social factors. The social factors tended to negatively affect professional identity whereas the factors of the three other dimensions exerted influence in different directions. A framework was established based on PI levels in different career stages of nurses to depict the continuum and dynamic nature of the development process. The PI development in nursing is a dynamic process shaped by multidimensional factors. Changes in policy should be made to reverse the nursing profession stereotype of being an assistant role to medicine. •Construction of professional identity in nursing is influenced by multidimensional factors.•Social attitudes toward nursing exert negative impacts on professional identity development.•Advancement in nursing professional proficiency does not necessarily lead to heightened professional identity.•Nursing students and clinical nurses in China display an overall low passion for nursing.